Seismic Activity of the Tarbela Dam Site and Surrounding Region - Seeber, L; Armbruster, J.; Farharullah, S. (Journal of Himalayan Earth Sciences, 1980)
The earthquake activity associated with the major faults of the Himalayan front in the Hazara arc region, including Tarbela dam, is discussed in terms of the active tectonic structure of this front. Moreover, the earthquake potential at the Terbela site arising from the Indus fault system is evaluated by extrapolating the earthquake magnitude distribution. The active tectonics associated with plate convergence in the Hazara arc region of the western Himalayas has been modeled primarily by using earthquake data from the seismic network centered at Tarbela. The near-surface structural trends in Hazara arc distinct and separated from the trend along the Himalayan front in Kashmir by the Hazara-Kashmir syntaxis. In contrast, the deeper structures which are active within the basement in Hazara are continuous with, and linear extensions of the northwest trending structures o the Himalayas in Kashmir. Thus, the arcuate structures in Hazara are only thin-skin. A major detachment fault decouples the sedimentary and metasedimentary layer of the thrust-and- fold belt from the underlying basement. The relative motion on the detachment obtained from seismic data is consistent with the southward vergence of the structures in this belt. Three families of active faults are recognized as potential sources of destructive earthquakes I the Hazara arc region and, in particular, at the Tarbela dam site: the basement faults; the detachment faults; and faults within the sedimentary layers. Available intensity and instrumental data indicate that the Himalayan Basement thrust and associated transverse or tear faults are the locus of most of the epicenters, however, the largest (M>=8) and most damaging earthquakes occur on the Himalayan Detachments. The Hazara arc included in the tectonic province of the Himalayan front, thus the Basement Thrust and the Detachment are identified with corresponding structures in Hazara, and the earthquake potential is estimated accordingly. A layer of thick infracambrian salt is associated with the Detachment in the Hazara arc redoing. The low-strength properties of this layer may cause the slip on this portion of the Detachment to occur aseismically. In this case, major Detachment earthquakes analogous to these known from the central section the Himalayan front would not be expected in the Hazara region. The sedimentary layer in the Tarbela network region of the Hazara arc is mostly aseismic except for Tarbela seismic zone (TSZ), centered near the Tarbela dam site. This sharply defined volume of seismicity is probably associated with anomalous rock properties rather than an isolated zone of crustal deformation. Thus, the faults active within the TSZ may slip aseismically in the sedimentary layer outside the TSZ. The maximum credible earthquake in the TSZ is assigned a magnitude 6.5, a maximum surface acceleration of 0.5g, and is associated with the surface of one of the faults in the Indus Valley a the Tarbela site. From a quantitate study of earthquake-magnitude distribution a repetition time of 1200 years is obtained for the maximum credible event. This implies a probability of 1/24 that this event will occur during a 50-year life-time of the dam. The maximum probable earthquake at the Tarbela site is 50 years is a M=5.5 event. This rate of seismicity along the Indus fault system at the Tarrbela site is 50 times higher than the average seismicity for the Hazara arc region. However, the level of seismicity on the TSZ is well below the seismicity associated with some of the other seismic zones within the Hazara arc. Most prominent among these is the IKSZ.